(untitled) (International conference on multidisciplinary science, 2026)
This thesis examines the methodology for developing creativity skills in primary school students through natural science subjects. Creativity plays an essential role in the cognitive and creative activities of students. The study presents theoretical foundations and practical approaches to developing creativity, methods of their implementation in primary education within natural sciences context, as well as an analysis of STEAM approach, problem-based learning, experimental activity and innovative technologies. Based on scientific sources, the thesis suggests effective methods and pedagogical techniques for fostering creativity.